(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Entrepreneurship education has emerged as a crucial component of modern education systems. It empowers students with the skills, knowledge, and mindset necessary to become innovative problem-solvers and future business leaders. However, the successful implementation of entrepreneurship education heavily relies on the perception and commitment of teachers. This article delves into the significance of teachers' perceptions of entrepreneurship education curriculum and its implications on its effective implementation at the senior secondary level. Teachers' perceptions of entrepreneurship education can significantly influence their teaching practices and students' learning outcomes. A positive perception can lead to enthusiastic teaching, fostering a conducive learning environment, and motivating students to embrace entrepreneurial endeavors. Conversely, a negative perception can hinder the effective implementation of the curriculum, leading to a lackluster learning experience and limited student engagement. Several factors contribute to teachers' perceptions of entrepreneurship education. These include their prior knowledge and experience of entrepreneurship, their beliefs about the relevance of entrepreneurship education, and their confidence in teaching entrepreneurial skills.